Determination of free serotonin and its metabolite 5‐HIAA in blood human samples with consideration to pre‐analytical factors. (14th April 2014) - Yubero‐Lahoz, Samanta; Rodríguez, Joan; Faura, Anna; Pascual, Julio; Oliveras, Anna; Cao, Higini; Farré, Magí; de la Torre, Rafael
ABSTRACT Significant differences have been reported over the years in measuring physiological levels of free circulating serotonin (f5‐HT) in platelet‐poor plasma (PPP). This work shows that there are crucial pre‐analytical factors in sample manipulation that can provoke an artifactual release of 5‐HT from platelets, and that, even when the sample is accurately processed to obtain PPP, f5‐HT levels are approximately 2.8 times higher than those of f5‐HT in blood. An alternative methodology consisting of ex vivo blood microdialysis coupled to high‐performance liquid chromatography–electrochemical detection is proposed and validated. It is considered the most accurate technique to measure physiological circulating f5‐HT and its metabolite 5‐hydroxyindoleacetic acid (f5‐HIAA), owing to its sensitivity (limits of quantification of 0.08 ng/mL) and reliability since there is no sample manipulation. The f5‐HT and f5‐HIAA levels in blood and in PPP were studied in control subjects, hypertensive and end‐stage renal disease patients, who have a deregulated serotonergic system. This work reveals that blood is the best matrix to determine f5‐HT concentrations, and the clinical relevance of the accuracy of f5‐HT determination is discussed. Copyright © 2014 John Wiley & Sons, Ltd.